Identification of Loading and Unloading Risks at a Container Depot Using the Bowtie Analysis Method - Hidayat Makarim; Willy Tambunan; Muriani Emelda Isharyani (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Loading and unloading activities at container depots are critical components of the logistics chain and pose significant risks to worker safety and operational continuity. Most port-related accidents are associated with cargo transportation and uncontrolled loading and unloading operations. This study aimed to identify and visualize the causes and risk consequences of loading and unloading activities at a container depot using the Bowtie Analysis method. A semi-quantitative approach was employed through field observations, interviews, and risk assessment at a container depot in Samarinda, East Kalimantan, from March to April 2026. Risk assessment was conducted using a 5x5 matrix based on likelihood and severity levels. The results identified three medium-category risks with a risk score of 6, namely operational disruption caused by handling equipment, fraud during manual unloading operations, and fraud during manual loading operations. The findings highlight that effective risk identification and visualization, strong coordination, workforce competency improvement, and the implementation of an optimal work system are essential to minimizing operational risks, maintaining business continuity, and enhancing competitiveness in the logistics industry.